2015
DOI: 10.1089/aid.2015.0134
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Circulating Soluble Tumor Necrosis Factor-α Receptors 1 and 2 with Interleukin-6 Levels in an Aging Cohort of Injection Drug Users with or at High Risk for HIV Infection

Abstract: Chronic inflammation marked by elevated interleukin (IL)-6, soluble tumor necrosis factor (TNF)-α receptor (sTNFR)-1, and sTNFR-2 levels may play a detrimental role in aging and HIV infection. This study aimed to evaluate the relationships of circulating IL-6 with sTNFR-1 and sTNFR-2 levels in an aging cohort of injection drug users (IDUs) with or at high risk for HIV infection. The AIDS Linked to the Intravenous Experience (ALIVE) study is a community-recruited, prospective observational study of former and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…By successfully targeting this upstream mediator, monoclonal antibodies against TNF-a have now become an indispensable armamentarium to treat rheumatoid arthritis. 9,56 In another analysis, when serum neopterin and CRP levels were added to the analysis described above, 55 we observed that neopterin was differentially associated with sTNFR-1 and sTNFR-2 rather than IL-6 or CRP. 57 These findings indicate that neopterin, being a mediator of immune activation, is associated with more proximal inflammatory mediators (sTNFR-1 and sTNFR-2) instead of distal mediators (IL-6 and CRP), suggesting a potential interventional target upstream of CRP and IL-6 that deserves further investigation.…”
Section: Interventionmentioning
confidence: 74%
See 1 more Smart Citation
“…By successfully targeting this upstream mediator, monoclonal antibodies against TNF-a have now become an indispensable armamentarium to treat rheumatoid arthritis. 9,56 In another analysis, when serum neopterin and CRP levels were added to the analysis described above, 55 we observed that neopterin was differentially associated with sTNFR-1 and sTNFR-2 rather than IL-6 or CRP. 57 These findings indicate that neopterin, being a mediator of immune activation, is associated with more proximal inflammatory mediators (sTNFR-1 and sTNFR-2) instead of distal mediators (IL-6 and CRP), suggesting a potential interventional target upstream of CRP and IL-6 that deserves further investigation.…”
Section: Interventionmentioning
confidence: 74%
“…We conducted an analysis to evaluate the relationships between serum levels of IL-6 and sTNFR-1 and sTNFR-2 in the AIDS Linked to the Intra Venous Experience study, a large prospective cohort study of injection drug users, and found significant associations of IL-6 with sTNFR-1 and sTNFR-2. 55 This finding has led to the notion that TNF-a may serve as a key mediator that triggers or regulates the inflammatory pathway in CLIP with therapeutic implications. This is because TNF-a is a central player in the inflammatory cascade leading to systemic inflammation.…”
Section: Interventionmentioning
confidence: 99%
“…Of note, CLIP encompasses many molecular mediators, likely forming a complex and interactive network. In fact, analyses of five CLIP mediators measured in the ALIVE study at baseline demonstrate that while soluble TNF-α receptors I and II levels were highly associated with IL-6 levels [46], levels of neopterin, an upstream immune activation mediator, was associated only with levels of soluble TNF-α receptors I and II levels, not with those of more distal and downstream inflammatory mediators IL-6 and CRP [47], suggesting potential a network of upstream vs downstream or proximal vs distal CLIP mediators in HIV infection with therapeutic implications.…”
Section: Frailty Aging Immunity and Hiv Infectionmentioning
confidence: 99%
“…In the ALIVE study, we have also shown significant associations of serum levels of IL-6 and sTNFR-1 as well as an aggregate inflammatory index including IL-6 and sTNFR-1 levels with frailty and mortality ( 38 ). In addition, we have demonstrated significant in vivo associations between IL-6 and sTNFR-1 and sTNFR-2 levels ( 39 ). However, these are primarily biomediators of chronic inflammation.…”
Section: Introductionmentioning
confidence: 99%